Epithelium‐specific MyD88 signaling, but not DCs or macrophages, control acute intestinal infection with Clostridium difficile. Issue 5 (10th March 2019) - Mamareli, Panagiota; Kruse, Friederike; Friedrich, Christin; Smit, Nathiana; Strowig, Till; Sparwasser, Tim; Lochner, Matthias
Abstract: Infection with Clostridium difficile is one of the major causes of health care acquired diarrhea and colitis. Signaling though MyD88 downstream of TLRs is critical for initiating the early protective host response in mouse models of C. difficile infection (CDI). In the intestine, MyD88 is expressed in various tissues and cell types, such as the intestinal epithelium and mononuclear phagocytes (MNP), including DC or macrophages. Using a genetic gain‐of‐function system, we demonstrate here that restricting functional MyD88 signaling to the intestinal epithelium, but also to MNPs is sufficient to protect mice during acute CDI by upregulation of the intestinal barrier function and recruitment of neutrophils. Nevertheless, we also show that mice depleted for CD11c‐expressing MNPs in the intestine display no major defects in mounting an effective inflammatory response, indicating that the absence of these cells is irrelevant for inducing host protection during acute infection. Together, our results highlight the importance of epithelial‐specific MyD88 signaling and demonstrate that although functional MyD88 signaling in DC and macrophages alone is sufficient to correct the phenotype of MyD88‐deficiency, these cells do not seem to be essential for host protection in MyD88‐sufficient animals during acute infection with C. difficile . Abstract : Host defense against Clostridium difficile depends on MyD88 signaling. We show here that intestinal epithelium‐specific MyD88 activation was sufficient to induce neutrophil recruitment and to protect mice during acute C. difficile infection, while depletion of mononuclear phagocytes, including macrophages and dendritic cells, did not enhance susceptibility toward the infection.